Operation and Maintenance Costs in Reverse Osmosis Desalination Projects Adopting Public-Private Partnerships: A Comprehensive Investigation and Analysis - Khairy, Mayar Mohamed (AUC Knowledge Fountain, 2025)
Water Desalination projects, specifically ones adopting reverse osmosis (RO) technology, play a pivotal role in addressing the scarcity of water globally. Since these projects require huge investments, there is an imperative need to focus on the role of public-private partnerships (PPPs) in their developments. This research tries to provide a comprehensive investigation into the factors affecting O&M costs in PPP desalination projects due to their importance. A comprehensive research approach, including a literature review, expert interviews, survey analysis, and statistical tools, is adopted in this research aiming to identify key factors and recommendations based on best practices in O&M costs under the PPP arrangements in Egypt. The research adopts a qualitative and quantitative analysis methodology. First, it starts with a systematic desktop literature review and engagement with subject matter experts (SMEs), specifically in the field of RO desalination, through interviews to capture different perspectives and insights into the nature of O&M cost dynamics, along with a framework and recommendation for PPP arrangements within the desalination field. Second, a survey is to be developed and distributed to gather data on RO desalination projects while considering experts’ opinions. Third, an analysis is to be conducted using statistical modeling techniques such as the relative importance index (RII) and exploratory factor analysis (EFA) to validate the significance of identified factors through a statistical package for social sciences (SPSS). In this research, an initial set of 34 key factors influencing the O&M costs of RO desalination projects is identified through a systematic literature review of published research papers, reports, and case studies and is categorized based on logical analysis into 5 main categories. This list is subsequently refined through several expert interviews, culminating in a final list of 33 factors. Additionally, interviews and surveys are conducted with 73 industry experts to assist in the research statistical findings. Thereafter, this research employs the RII as an analytical technique to determine the weighted rank of each item and its contribution to overall O&M costs. Factors related to RO desalination plant system and management and financial factors are among the primary categories that determine O&M costs and are ranked to have the highest influence on the previously mentioned costs. Moreover, it is revealed from the analysis that the factors that have the highest impact on O&M costs can be summarized, but not limited to, as follows: water quality parameters, membrane replacement rate, design considerations, lack of trained maintenance personnel, and energy consumption, with two factors with the lowest contribution: accommodation and spare parts. Moving to EFA, 15 trials are conducted for the EFA. The final trial for the EFA is conducted on 13 factors that have a high influence on O&M costs. The KMO test and Bartlett test are performed and show the adequacy of the data for further analysis. A total of 4 components are extracted, collectively explaining approximately 60% of the overall variation in the dataset. In addition to the analytical analysis for the O&M factors, this research proposes a comprehensive roadmap related to PPP desalination projects based on best practices from similar neighboring countries. This roadmap may serve as a guideline for addressing Egypt’s desalination PPP projects. Last but not least, this research explores the arrangement of desalination plants under the PPP framework through a qualitative analysis of relevant literature on the topic published from 2002 to 2023 to provide a strategic roadmap for such projects in Egypt where several recommendations are provided and divided into four areas: legal, financial and economic, technical, and managerial along with a SWOT analysis.